English phonetics and pronunciation practice - Carley, Paul (Routledge, 2018)
Includes bibliographical references and index; "English Phonetics and Pronunciation Practice provides a unique introduction to basic articulatory phonetics for students of English. Built around an extensive collection of practice materials, this book teaches the pronunciation of modern standard non-regional British English to intermediate and advanced learners worldwide. This book: provides an up-to-date description of the pronunciation of modern British English; demonstrates the use of each English phoneme with a selection of high-frequency words, both alone and in context in sentences, idiomatic phrases and dialogues; provides examples and practice material on commonly confused sounds, including illustrative pronunciation diagrams; is supported by a companion website featuring phonetic transcriptions and over 30 hours of practice audio material to check your pronunciation against; can be used not only for studying pronunciation in the classroom but also for independent student practice"--Amazon.com